PdII insertion-triggered meso-carbon extrusion of N-fused pentaphyrin to form N-fused sapphyrin PdII complexes. Issue 24 (24th February 2021) - Nakai, Akito; Yoneda, Tomoki; Tanaka, Takayuki; Osuka, Atsuhiro
Abstract : meso -Carbon extrusion reaction was found in the N-fused [22]pentaphyrin(1.1.1.1.1) scaffold upon Pd II insertion to give N-fused [22]pentaphyrin(1.1.1.1.0) ( i.e. [22]sapphyrin) Pd II complexes. Abstract : meso -Carbon extrusion of N-fused [22]pentaphyrin(1.1.1.1.1) occurred upon its Pd II complexation, giving N-fused [22]pentaphyrin (1.1.1.1.0) ([22]sapphyrin) Pd II complexes 5 and 6 as 22π aromatic compounds. Oxidation of 5 with DDQ and Sc(OTf)3 gave directly C–N linked dimer 7 .